Dancing with daddy - Schulte, Anitra Rowe (Two Lions, 2021)
Elsie can't wait to go to her first father-daughter dance. She picked out the perfect dress and has been practicing swirling and swaying in her wheelchair. Elsie's heart pirouettes as she prepares for her special night. With gestures, smiles, and words from a book filled with pictures, she shares her excitement with her family. But when a winter storm comes, she wonders if she'll get the chance to spin and dance her way to a dream come true.